The Ashley Madison affair. (September 2015) - Mansfield-Devine, Steve
Abstract: Of all the recent large-scale data breaches, of which there have been many, the Ashley Madison 'hack' has attracted the most interest and the greatest number of column inches in the press. And it's not hard to see why: there is a prurient element in watching the personal details of people who have used a site dedicated to infidelity being exposed to public gaze. But it is significant in other ways, too – not least because of the sheer scale of the leak and the nature of the data, from payment card transactions to source code. Of all the recent large-scale data breaches, the Ashley Madison 'hack' has attracted the most interest and the greatest number of column inches in the press. There is a prurient element, but it is significant for simple technical reasons too – to do with the sheer scale of the leak and the nature of the data, from payment card transactions to source code. Steve Mansfield-Devine details the story as it has unfolded so far and examines some of the more significant aspects.